Decreased maternal serum acetate and impaired fetal thymic and regulatory T cell development in preeclampsia - Mingjing Hu (Nature Portfolio, 2019)
Maternal immunological dysregulation might affect the immunological development of the fetus. Here the authors show that decreased maternal acetate is associated with preeclampsia, impaired fetal thymic output and regulatory T cell development.